Transcriptomic analysis of skin pigmentation variation in the Virginia opossum (Didelphis virginiana). Issue 12 (4th June 2018) - Nigenda‐Morales, Sergio F.; Hu, Yibo; Beasley, James C.; Ruiz‐Piña, Hugo A.; Valenzuela‐Galván, David; Wayne, Robert K.
Abstract: Skin pigmentation and coat pigmentation are two of the best‐studied examples of traits under natural selection given their quantifiable fitness interactions with the environment (e.g., camouflage) and signalling with other organisms (e.g., warning coloration). Previous morphological studies have found that skin pigmentation variation in the Virginia opossum ( Didelphis virginiana ) is associated with variation in precipitation and temperatures across its distribution range following Gloger's rule (lighter pigmentation in temperate environments). To investigate the molecular mechanism associated with skin pigmentation variation, we used RNA‐Seq and quantified gene expression of wild opossums from tropical and temperate populations. Using differential expression analysis and a co‐expression network approach, we found that expression variation in genes with melanocytic and immune functions is significantly associated with the degree of skin pigmentation variation and may be underlying this phenotypic difference. We also found evidence suggesting that the Wnt/β‐catenin signalling pathway might be regulating the depigmentation observed in temperate populations. Based on our study results, we present several alternative hypotheses that may explain Gloger's rule pattern of skin pigmentation variation in opossum, including changes in pathogen diversity supporting a pathogen‐resistant hypothesis, thermal stress associated with temperate environments, and pleiotropic and epistatic interactions between melanocytic and immune genes.